Validation of sterilization of Lucilia cuprina larvae using raw honey through scanning electron microscope - Nur Afrina MH; Santhana Raj L; Nur Fateha R; Wan Nur Alia WZ; Kamesh R; Nazni WA (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2019)
Background: In the application of Maggot Debridement Therapy (MDT), sterilized maggots (Lucilia cuprina) by standard chemicals were used. Recent potential demands for using a procedure with allnatural products, raw honey has been proposed as a natural sterilization technique to replace the chemical products. Methods: Lucilia cuprina collected from a laboratory colony were divided into treated group (sterilized) and control group (non-sterilized) to undergo sterility testing with honey dilution. Scanning electron microscope (SEM) was used to examine and ascertain the sterility of honey dilution. SEM provided direct observation of microorganism's presence on external surface L. cuprina after sterilization by disinfectants of raw honey (tualang honey).